Income taxation of couples and the tax unit choice - Helmuth Cremer; Jean-Marie Lozachmeur; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper studies the optimal non linear income tax of couples. We build a general unitary model of labor supply and allow multidimensional heterogeneity in a discrete type framework. We concentrate our analysis on the resulting intra-family labor allocation of labor supplies and show that this analysis is strongly related to the choice of the tax unit (individual versus joint taxation). We give a necessary condition to have fully joint taxation in this framework and discuss some examples.
Keywords: H21; H31; D13; 330; Familienbesteuerung; Haushaltsökonomik; Optimale Besteuerung; Theorie